Educating children with special needs : current trends in school policies & programs - Cchadha, Anupriya (New Delhi : A.P.H publishing, 2012)
This book has been written for regular classroom teachers, special education teachers, other school personnel (such as school psychologists, counsellors, social workers, administrators, and so on), parents and prospective teachers. It provides basic information.
Keywords: Children with disabilities; Autistic children -- Education